PENGARUH KONFLIK PERAN GANDA, STRESS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MALANG - Ayu Yuslihanah; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of this research is to describe dual role conflict, work stress, work environment, and employee performance and to know the influence of dual role conflict, work stress, and work environment to partially and simultaneously employee's performance. This research method using quantitative method. This type of research is survey research.The sample of this research is employees of the Office of Population and Civil Registry of Malang Regency that is as many as 39 respondents. Methods of data collection using questionnaires. The method of analysis used in this study is multiple regression analysis with SPSS 14.0 for windows.The results of this study indicate that dual role conflict, work stress, and work environment partially and simultaneously affect the performance of employees of the Office of Population and Civil Registry of Malang Regency. Keywords : Dual Role Conflict, Work Stress, Work Environment and Employee Performance.